Kajian Analisis Lalulintas Simpang Bersinyal di By Pass Krian Untuk Perencanaan Pelebaran Jalan dan Fly Over - Wibisono, R. Endro; Muhtadi, Adhi; Cahyono, Donny (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2019)
Krian Bypass intersection is a very crowded route because of its location near Sidoarjo and Mojokerto Regencies for the economic distribution of Surabaya City. There needs to be phase regulation, road widening or fly over so that the intersection traffic volume is not getting saturated. As a benchmark is the forecasting of traffic performance carried out for 3 years from 2018 to 2021. Based on the results of forecasting, the Krian Bypass intersection will decrease its DS value by widening the road so that the green time cycle will be low and turn right impact the DS value below 1 (one). The lowest 2018 DS is 1.61, while the highest DS is 2.49. While the lowest year 2021 DS is 2.72, while the highest DS is 4.85. For the solution with the right turn phase for each intersection to the north DS = 1.02, U-RT = 0.82, S = 1.38, S-RT = 0.69, T = 1.24, T-RT = 0.78, B = 1.79, B-RT = 0.04 . The solution for forecasting the flow of Krian Bypass in 2021. The calculation results made with effective width engineering, turn right and green time can reduce the DS value (Degree of Saturation) still shows DS value> 0.75 - 1, then fly over is constructed with a scenario of 20% vehicles through existing and 80% of vehicles through fly over. Year 2021 The impact of fly over shows North DS = 0.4, South = 0.51, East = 0.56, and West = 0.45